2015
DOI: 10.5606/kbbihtisas.2015.01947
|View full text |Cite
|
Sign up to set email alerts
|

New predictive parameters of nasal polyposis: neutrophil to lymphocyte ratio and platelet to lymphocyte ratio

Abstract: Neutrophil to lymphocyte ratio value may be used as a novel marker that is easily administered in patients with nasal polyps and obtained with low-cost tests. New studies with larger patient series are needed for the value of PLR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
0
14
0
3
Order By: Relevance
“…In patients with Bell's palsy, PLR was reported to be higher than control subjects. [23] In a study of Atan et al, [24] there was statistically no significant difference in terms of mean PLR values between patients with nasal polyposis and healthy individuals. PLR was found to be superior to NLR as an inflammation marker in some studies.…”
Section: Ent Updatesmentioning
confidence: 87%
“…In patients with Bell's palsy, PLR was reported to be higher than control subjects. [23] In a study of Atan et al, [24] there was statistically no significant difference in terms of mean PLR values between patients with nasal polyposis and healthy individuals. PLR was found to be superior to NLR as an inflammation marker in some studies.…”
Section: Ent Updatesmentioning
confidence: 87%
“…In the study of Atan et al (9), they found significantly higher leucocyte and thrombocyte counts in bilateral sinonasal polyposis than in the healthy control group. They also found higher TLR, but that was not significant.…”
Section: Discussionmentioning
confidence: 89%
“…He also suggested that by using NLR, unnecessary surgery could be avoided. It has also been shown that NLR could be used as a predictive marker in the patients with obstructive sleep apnea and nasal polyposis (20,21). High NLR has been shown to indicate poor prognosis in patients with sudden hearing loss (22,23).…”
Section: Discussionmentioning
confidence: 99%